Thermal efficiency extends distance and variety for honeybee foragers: analysis of the energetics of nectar collection and desiccation by Apis mellifera. Issue 150 (31st January 2019) - Mitchell, Derek
Abstract : The desiccation of nectar to produce honey by honeybees ( Apis mellifera L.) is an energy-intensive process, as it involves a quasi-isothermal change in the concentration of sugars from typically 20 to 80% by vaporization (honey ripening). This analysis creates mathematical models for: the collected nectar to honey ratio; energy recovery ratio; honey energy margin; and the break-even distance, which includes the factors of nectar concentration and the distance to the nectar from the nest; energetics of desiccation and a new factor, thermal energy efficiency (TEE) of nectar desiccation. These models show a significant proportion of delivered energy in the nectar must be used in desiccation, and that there is a strong connection between TEE and nest lumped thermal conductance with colony behaviour. They show the connection between TEE and honeybee colony success, or failure, in the rate of return, in terms of distance or quality of foraging. Consequently, TEE is a key parameter in honeybee populations and foraging modelling. For bee keeping, it quantifies the summer benefits of a key hive design parameter, hive thermal conductance and gives a sound theoretical basis for improving honey yields, as seen in expanded polystyrene hives.